Factors associated with the lack of antiretroviral therapy initiation among eligible HIVpositive pregnant women in Swaziland - G Louwagie; C Chouraya; B Nhlabatsi; M Mahdi; B Girdler-Brown (South African Medical Association, 2017)
Background. Antiretroviral therapy (ART) initiation is critical for the prevention of mother-to-child transmission (PMTCT) of HIV.Objectives. To quantify factors that were barriers or facilitators to the initiation of ART in pregnant HIV-infected women in Swaziland.Methods. We conducted a cross-sectional survey in HIV-infected women with at least one antenatal care (ANC) visit, who had delivered in maternity wards between April and August 2013 in Swaziland. Variables collected included intrapersonal, interpersonal and organisational factors. Logistic regression models were used to calculate univariate and adjusted multivariate measures of association between ART initiation and the independent variables.Results. Among the 163 pregnant women who were eligible for ART, 110 (67.5%) were initiated on ART by the time of delivery. The most commonly cited reason for not initiating ART (n=53) was women not being ready to initiate life-long treatment (24.5%). On multivariate logistic regression, favourable perceptions of the benefits of ART (adjusted odds ratio (AOR) 3.04; 95% CI 1.55 - 5.96) and presence of partner support (AOR 4.75; 95% CI 2.11 - 10.67) remained significantly and independently associated with ART initiation.Conclusion. ART initiation among ART-eligible pregnant women in Swaziland was independently associated with the presence of partner support and favourable perceptions of the benefits of ART. Stronger counselling and education for pregnant women and male involvement strategies need to be implemented as universal life-long ART for all HIV-infected pregnant women is implemented.